Numerical simulation of the effect of synthetic jet actuators on aerodynamic performance in high-lift device configurations - Yamin, Mohamad; Apriyadi, Kukuh Ivan; Firmansyah, Riyan (Jurnal Polimesin, 2025)
The aviation industry faces significant challenges in reducing environmental impacts, particularly fuel consumption and  noise pollution.  To  address  these  issues,  various  aerodynamic optimization and flow control technologies have been developed to enhance aircraft efficiency. One promising approach is Active Flow Control (AFC), particularly in wing-flap configurations. However, cambered flaps can induce flow separation, leading to increased drag and reduced aerodynamic performance. This study investigates the application of AFC using Zero Net Mass Flux (ZNMF) to mitigate flow separation and improve aerodynamic efficiency. Numerical simulations were conducted using ANSYS Fluent, employing the Delayed Detached Eddy Simulation –Spalart-Allmaras (DDES-SA) turbulence model to accurately capture flow separation and vortex structures. The research explores a novel ZNMF geometry, analyzing different frequency and velocity parameters to determine the optimal settings for suppressing flow separation. The results demonstrate that  the  Synthetic  Jet  Actuator  (SJA)  significantly enhances aerodynamic efficiency by optimizing the CL/CD  ratio through drag reduction without major lift loss. Optimal performance is achieved at frequencies of 150–300 Hz and jet velocities of ≥150 m/s, stabilizing airflow, reducing flow separation, and suppressing vortex formation. At an AOA of 0°, a frequency of 100 Hz provides the greatest CL reduction, while at an AOA of 10°, frequencies of 100–250  Hz  substantially improve  the  CL/CD   ratio.  This  study confirms that SJA is an effective strategy for drag reduction and aerodynamic optimization. These findings highlight its potential to improve aircraft performance, reduce fuel consumption and CO₂ emissions, and contribute to more sustainable aviation technology